Reflections and Recommendations on the Identity and Language (Northern Ireland) Bill 2022 / Machnaimh agus Molta ar an mBille Finilachta agus Teanga (Tuaisceart ireann) 2022 - Costello, Risn (My University, 2023)
The 2022 Bill represents a ‘first generation’ piece of minority language legislation in that it neither seeks to impose strict, rights-based standards nor punitive deterrent sanctions. In this respect, the legislation falls short of the legislative standards promised under the St Andrew’s Agreement and which activists within the jurisdiction have called for as well as the legal provisions that COMEX has urged must be implemented in order for the United Kingdom to comply with its obligations under the ECRML. This divergence was, however, characterised by participants as being part of the necessary compromise to ensure that Irish is not viewed as an externally imposed obstacle and does not retrench resistance to minority languages. The Bill as it was introduced before the House of Lords lacks clarity in both its objectives and the measures and mechanisms through which it proposes to achieve them, and is characterised by a recourse to political approval and general policy which lacks the specificity of comparable legislation in other jurisdictions in the UK and on the island of Ireland. The main function of the Bill, and its incontrovertible success, is its provision of legal and institutional recognition of Irish as a language within Northern Ireland. This may, in certain respects, seem to be a moderate, or even insufficient, achievement. However, it is significant for three reasons: First, it provides a new status quo in accordance with which it may gradually become not only unremarkable but expected to encounter Irish in institutional settings and in which engagement with the language may, as a result, become progressively apolitical. Second, and relatedly, the Bill affirms the existence of a multilingual population within the jurisdiction and recognises their entitlement (albeit not in the language of rights) to affirm their linguistic identity not only in private spaces but in public ones. These are both significant developments on an individual basis for Irish speakers but also at a societal level for advancing reconciliation in a manner which Third, and finally, the proposed legislation would provide an institutional model which can be developed further by amendment to comply more fully with the requirements of the ECRML. In this respect, the proposed legislation may operate as a minimum benchmark which will be hard to displace.
PUBLISHED
Keywords: Irish language, Legislation; Irish language, Northern Ireland; Minority languages, Legislation; Identities in Transformation; Making Ireland; Language Rights